2r+12=3r-2r

Simple and best practice solution for 2r+12=3r-2r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2r+12=3r-2r equation:


Simplifying
2r + 12 = 3r + -2r

Reorder the terms:
12 + 2r = 3r + -2r

Combine like terms: 3r + -2r = 1r
12 + 2r = 1r

Solving
12 + 2r = 1r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-1r' to each side of the equation.
12 + 2r + -1r = 1r + -1r

Combine like terms: 2r + -1r = 1r
12 + 1r = 1r + -1r

Combine like terms: 1r + -1r = 0
12 + 1r = 0

Add '-12' to each side of the equation.
12 + -12 + 1r = 0 + -12

Combine like terms: 12 + -12 = 0
0 + 1r = 0 + -12
1r = 0 + -12

Combine like terms: 0 + -12 = -12
1r = -12

Divide each side by '1'.
r = -12

Simplifying
r = -12

See similar equations:

| 5x+2(7-2x)=22 | | X-20/1000=23 | | X+(X*0.06)=5.85 | | 7(1-3c)=7-(7c+2) | | X-20/100=23 | | 5(t-3tv)= | | 23/.8 | | 6w^2+7w+2= | | 60r-50=12-2 | | 23/1-.20 | | 23/1-.20=x | | 2/5=2(3x-7) | | 2/5=2(3x-7 | | -5x+68=-32-7x | | 2r+2=3(r-4) | | 4-18x^2=6x | | (3h+4)(2h-5)= | | 1/4-x=23 | | 3x(5-2x)=-6x(x+2)+81 | | =-6(h+3)-8(h-7) | | 106=6x+4(-3x+34) | | 1/3x^(2/3) | | 14x+30=12x-58 | | 0=1/3x^2/3 | | 5x+18=34 | | 0=-2(x-1) | | 2y=500-2x | | 2x=500-2y | | 132=-50-7x | | 0=2(x+2) | | 3.2x+2.3=-9.4 | | 9x-7=3x+12 |

Equations solver categories